2022
DOI: 10.1002/ejp.2043
|View full text |Cite
|
Sign up to set email alerts
|

‘That's what makes me better’: Investigating children and adolescents' experiences of pain communication with healthcare professionals in paediatric rheumatology

Abstract: Background Pain communication should be an integral part of clinical consultations, particularly in paediatric rheumatology where children and adolescents frequently present with chronic musculoskeletal pain. To date, literature exploring the nature of and extent to which pain communication occurs has focused on healthcare professionals as respondents, yielding inconsistent and incomplete findings. The aim of this study was to explore children and adolescents' experiences of pain communication in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 36 publications
5
10
0
1
Order By: Relevance
“…Caution will be required to ensure that CMP explanations do not become more heterogenous as clinicians move from simple biomedical interpretations of pain to a broader and more nuanced biopsychosocial perspective that incorporates pain complexity and reasons for persistence [1,2,64]. Lee et al found a range of effective and ineffective communication approaches among adolescents suffering from CMP conditions; similar to our study, they emphasized the importance of providing clear and tailored pain management advice for each individual [34]. Together with our results, this highlights the tremendous impact these mixed messages provided by clinicians have; we found adolescents reported their anxiousness was amplified, due to varying explanations and advice from clinicians [39,60].…”
Section: Explanations Of Findingssupporting
confidence: 76%
See 4 more Smart Citations
“…Caution will be required to ensure that CMP explanations do not become more heterogenous as clinicians move from simple biomedical interpretations of pain to a broader and more nuanced biopsychosocial perspective that incorporates pain complexity and reasons for persistence [1,2,64]. Lee et al found a range of effective and ineffective communication approaches among adolescents suffering from CMP conditions; similar to our study, they emphasized the importance of providing clear and tailored pain management advice for each individual [34]. Together with our results, this highlights the tremendous impact these mixed messages provided by clinicians have; we found adolescents reported their anxiousness was amplified, due to varying explanations and advice from clinicians [39,60].…”
Section: Explanations Of Findingssupporting
confidence: 76%
“…Clinicians were commonly described to use heterogeneous terminologies and explanations that did not fit with adolescents existing beliefs (i.e., perception of the cause of the pain and expected management) [39,46,60]. Heterogeneous and non-person-centered pain terminologies were highlighted as a core issue for children and adolescents' that impaired their ability to understand their pain [14,34]. Our findings concerning the role of diagnostic uncertainty in the qualitative studies shed light on a challenging area for clinicians, as it emphasizes the importance of clear communication between clinicians, adolescents, and their parents [34,44,46].…”
Section: Explanations Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations